Risk Factors Associated With Health Care Utilization in Preschool Recurrent Wheezers in a Tropical Environment - Muñoz, César; Guevara, Lissette; Escamilla, María-Isabel; Regino, Ronald; Acevedo, Nathalie; Escamilla-Arrieta, Jose Miguel (Frontiers in Allergy, 2021)
Introduction: The severity of wheezing episodes is related with the need for health services, but the factors associated with health care utilization in preschool recurrent wheezers in underdeveloped regions are unclear. Objective: To evaluate the factors associated with health care utilization in preschool recurrent wheezers in Cartagena, Colombia. Methods: One hundred twenty-seven recurrent wheezers (age 2–6 years old) who were admitted to the emergency room (ER) due to wheezing in a Pediatric reference hospital in Cartagena were included. Children were evaluated by means of questionnaires and classified according to the number of ER visits, need for hospitalization and history of intensive care unit (ICU) admission due to wheezing within the last year. Total serum IgE and specific IgE to house dust mite allergens (HDM) were measured by ImmunoCAP® and allergen sensitization was evaluated by skin prick tests (SPT). Results: The maternal report of nocturnal cough without fever in their children increased the risk to have ≥5 ER visits in the last year due to wheezing. The use of montelukast was negatively associated with hospitalization, while a history of pneumonia and lack of tap water, increased the risk of hospitalization due to wheezing. A history of bronchiolitis, family history of asthma, cohabiting with two or more siblings, passive exposure to smoke and lack of sewage facilities increased the risk of ICU admission due to wheezing. The presence of atopy evaluated by SPT reactivity, total IgE levels or specific IgE to HDM were not associated with health care utilization. We also found that seroprevalence of positive IgE (≥0.35 kU/L) was 27% to B. tropicalis and 20.3% to D. pteronyssinus but the prevalence of positive IgE sensitization to these allergens was below 2% and 8% when evaluated by SPT, respectively. Conclusions: Poverty indicators are associated with ICU admission in a group of preschool recurrent wheezers and should be considered as aggravating factors for wheezing. These factors must be systematically assessed in the medical approach in underdeveloped regions in the tropics. Nocturnal cough without fever is a symptom associated with frequent ER visits while atopy was not associated with health care utilization in preschool recurrent wheezers.